2018
DOI: 10.1017/s0959270918000060
|View full text |Cite
|
Sign up to set email alerts
|

Habitat selection of an endangered European farmland bird, the Ortolan BuntingEmberiza hortulana, in two contrasting landscapes: implications for management

Abstract: SummaryEffective conservation measures for any bird species across their distribution ranges require detailed knowledge of landscape-specific differences in habitat associations. The Ortolan Bunting Emberiza hortulana is a farmland bird species, which experienced massive population declines during the recent decades and has become a conservation priority in many European countries. Thus, identification of the key habitat features is an important prerequisite for the conservation of the species. Here we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…However, the negative effect of farmstead modernization was strongest for building‐nesters and noncrop‐nesters (that comprised 83% of the studied bird species), whereas we could not detect an effect on field nesters. Thus, our results do not apply to all groups of birds, stressing that other factors, such as multi‐scale habitat heterogeneity or presence of non‐farmed habitats (Šálek et al, 2019, 2021; Šálek, Hula, et al, 2018; von Post et al, 2012), might play an important role for the abundance, survival and reproductive success of these species. Consequently, factors related to landscape composition should still be taken into consideration in conservation strategies.…”
Section: Discussionmentioning
confidence: 70%
“…However, the negative effect of farmstead modernization was strongest for building‐nesters and noncrop‐nesters (that comprised 83% of the studied bird species), whereas we could not detect an effect on field nesters. Thus, our results do not apply to all groups of birds, stressing that other factors, such as multi‐scale habitat heterogeneity or presence of non‐farmed habitats (Šálek et al, 2019, 2021; Šálek, Hula, et al, 2018; von Post et al, 2012), might play an important role for the abundance, survival and reproductive success of these species. Consequently, factors related to landscape composition should still be taken into consideration in conservation strategies.…”
Section: Discussionmentioning
confidence: 70%
“…Conrads (1968) pointed out that the vegetation height within fields should not exceed 30 cm during the period of territory establishment. Moreover, Šalek et al (2019) found that an intermediate cover of bare ground was preferred by Ortolan Buntings. Accordingly, the negative effect of maize is due to its very sparse vegetation during the time of territory establishment in the study area (Bellenhaus and Fartmann 2009, Menz and Arlettaz 2011).…”
Section: Discussionmentioning
confidence: 99%
“…On average, territories of Ortolan Buntings are ~3 ha in size (Conrads 1969, Berg 2008, Glutz von Blotzheim 2011). However, for foraging, the birds also often use larger home ranges up to 30 ha (Dale and Olsen 2002, Šalek et al 2019). While adult Ortolan Buntings are mainly granivorous, nestlings strongly depend on invertebrate prey (mainly Lepidoptera larvae, Coleoptera, and Orthoptera) (Conrads 1969, Glutz von Blotzheim 2011, Menz and Arlettaz 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2016, 2017, Šálek et al . 2018). However, given the expansion of smallholders in Ethiopia (Central Statistical Agency (Ethiopia) and ICF International 2016) and their need for fire wood and timber (Fentie et al .…”
Section: Discussionmentioning
confidence: 99%